STEVIA REBAUDIANA: GLOBAL IMPORTANCE, DEVELOPMENT PROSPECTS, AND CULTIVATION OPPORTUNITIES IN UZBEKISTAN - M. U. Nishonalieva,; A. A. Qurbonov,; J. SH. Shavkiev, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: Stevia rebaudiana is a low-calorie natural sweetener widely used in the food and nutraceutical industries. This study analyzes its biologically active properties, market trends, breeding and agrotechnological approaches, as well as the prospects for cultivation in Uzbekistan. The results indicate that stevia is a promising crop for healthy nutrition and export-oriented production.